Pesticide-Induced Neurotoxicty Impacts Cholesterol Metabolism In Mouse Midbrain - Maniscalchi Velásquez, Athina del Valle (2024)
Maneb (MB) is a widely used dithiocarbamate fungicide that can cross the blood-brain barrier and has been reported as an environmental triggering factor of Parkinson’s disease. In a previous work, we demonstrated that MB exposure induced lipid peroxidation in neuronal cultures along with downregulation of glutathione peroxidase 4 (GPX4), and mitochondrial alterations. These previous findings were indicative markers of a specific regulated cell death mechanism named ferroptosis. In the present work, we aimed to characterize MB-induced neurotoxicity in midbrain using C57BL/6 mice exposed to the pesticide. In this in vivo model we studied biochemical changes associated with lipid metabolism. In the midbrain of MB-treated animals, oxidative stress and astrogliosis were accompanied by the loss of tyrosine hydroxylase-positive neurons, and an enhanced expression of α-synuclein. Regarding markers of ferroptosis, MB promoted lipid peroxidation with reduced glutathione content and decreased mRNA expression of GPX4 and the cystine/glutamate transporter SLC7A11. In addition, cholesterol accumulation was accompanied by the upregulation of genes associated with its metabolism, such as Srebp-2 and Hmgcr. Behavioral tests showed that MB treatment impaired mice's locomotor activity. The total distance traveled, supported and unsupported rears were lessened during the open field test in MB-treated mice, and they additionally displayed a diminished rotarod performance. Overall, we established a mouse model of pesticide exposure with a neurodegenerative phenotype that points towards a link between midbrain ferroptosis and colesterol metabolism disturbances.